Arabic Language Teaching and Learning in Muslim Minority of West Papua - Wekke, Ismail Suardi (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2017)
Islamic boarding school which well-known as pesantren establishment reflects a process of transformation on the religious level of education. The Arabic language is the compulsory subject to gain a set of curriculum. Therefore, it is a need to explore the process of Arabic language teaching and learning in an Islamic school. This research was conducted in Sorong's greater area of West Papua. In-depth interviews and non-participant observation were employed in collecting data. The Arabic language is the main subject to support other subjects. Each semester, students need to complete a set of subjects. Some activities extend the subject in many courses to enrich language skills and capacity. In addition, the Muslim minority is the environment to challenge the region. Therefore, the schools constructed the special program in complementing the syllabus. There is an additional program to complete in a year program. The combination of classroom activity and course program is the breakthrough to extend the opportunity to learn not only in the classroom but also outside the classroom. This article concludes that an additional program was created to enhance students’ skill and language development through practices and non-formal courses.